Voting Customs Acquisition of Land and Buildings (BPHTB) Suitable for Any Transitional Right Price Under Market Based on Pekalongan District Regulation No. 8 of 2010 - Nur Yanti; Indah Rachmawati; Gunarto Gunarto (Jurnal Akta, 2019)
One of the customs levied by the Government of the District / Municipal Customs on Acquisition of Land and Building (BPHTB). Its implementation in Pekalongan based Perwal Pekalongan No. 8 of 2010. The constraints faced in the implementation of Pekalongan Perwal No. 8 of 2010 of which are dishonesty customspayer, so do check the location of the object and the subject BPHTB Customspayers can not afford given the reductions and adjusted Customspayers with conditions.Keywords: BPHTB and Market Value.